Exercise and immunity: Beliefs and facts - López, P.; Chamorro-Viña, C.; Gómez-García, M.; Fernandez-del-Valle, M. (The active female. Health issues throughout the lifespan, 2023)
Exercise immunology is the field that studies the effects of exercise on the immune system. In the 1990s, Dr. Nieman formulated the controversial "J-shaped hypothesis" to describe the relationship between acute exercise intensity and the risk of acquiring infections, such as upper respiratory tract infections. This hypothesis suggested that moderate exercise has the ability to improve immune function above sedentary levels, while high intensity exercise depresses the immune system. Since then, current knowledge has exposed some methodological limitations, challenging the idea that any form of exercise can be considered "immunosuppressive". Overall, acute bouts of moderate exercise have shown to enhance immune-surveillance, while frequent exercise has been associated with an increased immunological competency. Actually, contemporary research interests are focused in understand how immune changes induced by exercise are able to reduce risk for common chronic diseases. To this end, the introduction of -omics approaches (metabolomics, proteomics, lipidomics, and metagenomics) is providing new insights on the interactions between exercise and immunity. In this chapter, we deep into the previous literature addressing the "immunity-exercise axis" in order to critically review the basis of the J-shaped curve and open window hypothesis. In addition, an overview of the components of the immune system and how are affected by exercise considering the gender dimension will help us to unravel the key role of regular physical activity in the prevention and treatment of disease.